Electrolyte system strategies for anionic ITP with ESI‐MS detection. 3. The ITP spacer technique in moving‐boundary systems and configurations with two self‐maintained ITP subsystems. Issue 5 (13th January 2014) - Gebauer, Petr; Malá, Zdena; Boček, Petr; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> This contribution is the third part of the project on strategies used in the selection and tuning of electrolyte systems for anionic ITP with ESI‐MS detection. The strategy presented here is based on the creation of self‐maintained ITP subsystems in moving‐boundary systems and describes two new principal approaches offering physical separation of analyte zones from their common ITP stack and/or simultaneous selective stacking of two different analyte groups. Both strategic directions are based on extending the number of components forming the electrolyte system by adding a third suitable anion. The first method is the application of the spacer technique to moving‐boundary anionic ITP systems, the second method is a technique utilizing a moving‐boundary ITP system in which two ITP subsystems exist and move with mutually different velocities. It is essential for ESI detection that both methods can be based on electrolyte systems containing only several simple chemicals, such as simple volatile organic acids (formic and acetic) and their ammonium salts. The properties of both techniques are defined theoretically and discussed from the viewpoint of their applicability to trace analysis by ITP‐ESI‐MS. Examples of system design for selected model separations of preservatives and pharmaceuticals illustrate the validity of the theoretical model and application potential of the proposed techniques by both computer simulations and experiments. Both new methods enhance the application range of ITP‐MS and may be beneficial particularly for complex multicomponent samples or for analytes with identical molecular mass.